2017
DOI: 10.1038/s41598-017-05627-z
|View full text |Cite
|
Sign up to set email alerts
|

X-ray crystallographic structure of a bacterial polysialyltransferase provides insight into the biosynthesis of capsular polysialic acid

Abstract: Polysialic acid (polySia) is a homopolymeric saccharide that is associated with some neuroinvasive pathogens and is found on selective cell types in their eukaryotic host. The presence of a polySia capsule on these bacterial pathogens helps with resistance to phagocytosis, cationic microbial peptides and bactericidal antibody production. The biosynthesis of bacterial polySia is catalysed by a single polysialyltransferase (PST) transferring sialic acid from a nucleotide-activated donor to a lipid-linked accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The characteristic elements of both folds are two Rossmann-like domains that are either tightly associated, forming a central, continuous β-sheet (GT-A), or opposed to each other, forming a deep cleft that contains the catalytic center (GT-B) ( 11 , 12 ). Polymerases with GT activity are either single-domain enzymes acting alone to synthesize a homopolymer ( 13 16 ) or, when generating a heteropolymer, acting in concert with another domain of the same GT fold type, which is either independently expressed ( 1 , 17 ) or part of the same polypeptide ( 18 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic elements of both folds are two Rossmann-like domains that are either tightly associated, forming a central, continuous β-sheet (GT-A), or opposed to each other, forming a deep cleft that contains the catalytic center (GT-B) ( 11 , 12 ). Polymerases with GT activity are either single-domain enzymes acting alone to synthesize a homopolymer ( 13 16 ) or, when generating a heteropolymer, acting in concert with another domain of the same GT fold type, which is either independently expressed ( 1 , 17 ) or part of the same polypeptide ( 18 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…56 A comparison of structural data of MhPST and a mammalian PST (ST8SiaIII) revealed that, although both enzymes create the same type of α-2 → 8-linked polySia chains, the enzymes share no common structural features. 57 In Neisseria meningitidis serogroups B (NmB) and C (NmC) and Escherichia coli K1, the polySia in the capsule is essential for virulence, making the polySia-producing enzymes a potential antimicrobial target. The structural differences between the bacterial and mammalians PSTs, leading to higher substrate promiscuity for the first, may aid in selective inhibitor development.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…Most studies have been focused on the biochemical synthesis of capsular polysaccharides and the molecular machines used to control the biosynthesis pathways. 14 Recent models have concluded that in the case of the E. coli K1 polysaccharide the capsular polysaccharide chains are made inside bacterial cells before transport across the periplasmic space onto the outer membrane. 15 In addition to biosynthesis mechanisms, bacterial capsular morphology has been observed on fixed bacterial surfaces using scanning electron microscopy, transmission electron microscopy, 16,17 and atomic force microscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to the high virulence of bacteria with capsular polysaccharides, the manipulation of polysaccharide production could have important medical benefits. Most studies have been focused on the biochemical synthesis of capsular polysaccharides and the molecular machines used to control the biosynthesis pathways . Recent models have concluded that in the case of the E.…”
Section: Introductionmentioning
confidence: 99%